Research Progress on Resource Utilization of Phosphate Tailings - Xie, Xuemin (International Journal of Natural Resources and Environmental Studies, 2026)
As a non-renewable strategic mineral resource, phosphate ore is the core raw material for phosphate fertilizer production, new material manufacturing and other fields. The high proportion of low and medium-grade phosphate ore in China leads to an annual emission of phosphate tailings (PT) exceeding 10 million tons, with a huge cumulative stockpile and low comprehensive utilization rate. The environmental and safety problems such as water pollution and geological hazards caused by stockpiling have become increasingly prominent. Under the requirements of the “dual carbon” strategy and circular economy development, the transformation of PT from stockpiling disposal to efficient resource utilization has become an inevitable trend. PT is rich in valuable components such as calcium, magnesium, phosphorus and silicon. At present, its resource utilization has formed four core technical paths: recovery of valuable elements, building material utilization, agricultural conversion, and preparation of environmental functional materials, showing good application potential in fields such as bulk consumption, nutrient reuse and pollution control. However, it still faces industrialization bottlenecks such as complex processes, low added value and poor adaptability of soil application. This paper systematically sorts out the current situation of PT generation and disposal, the environmental risks of traditional disposal, and the research progress of various resource utilization technologies, analyzes the advantages and limitations of different technical paths, and looks forward to its development direction of synergization, high-valueization, greenization and intelligence, in order to provide reference for the technological innovation and industrial landing of efficient resource utilization of PT and the construction of a closed-loop industrial chain.